Meningkatkan Keterampilan Guru SMP Kota Palu dalam Merancang Pembelajaran PBL Berbasis Understanding by Design - Gamar Shamdas; Mohammad Jamhari; Mursito Bialangi; Nengah Kundera; Rizka Fardha (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The community service program aims to use training and mentoring to help teachers at SMP Negeri 19 Palu, Central SSulawesi, become more adept at creating UbD-based PBL classes. The main problem is teachers' low competence in designing innovative learning, so interventions such as training, mentoring, and direct practice are needed. This activity is important in encouraging initiatives to raise the standard of education and teacher pedagogy. This program employs interactive action research techniques in a qualitative manner. Data were collected from 15 teachers through product assessments and assessments of teacher involvement and skills. The results were analyzed descriptively and qualitatively. The activity’s outcomes demonstrate a rise in teacher skills in designing learning using the UbD-based PBL model. 100% of the produced goods meet the